2021
DOI: 10.2217/rme-2020-0208
|View full text |Cite
|
Sign up to set email alerts
|

Industry Updates From the Field of Stem Cell Research and Regenerative Medicine in November 2020

Abstract: Latest developments in the field of stem cell research and regenerative medicine compiled from publicly available information and press releases from nonacademic institutions in November 2020.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…[ 88 ] Another unique feature of Matrion is that during rehydration it doesn't get folded or rolled up, thus having fewer chances of migration away from the injury site. [ 89 ] A current trial is underway to examine the safety and efficacy of Matrion in managing diabetic foot ulcers and lower extremity wounds. The trial involves 120 participants aged 21–80 years who have full‐thickness wounds due to Type I or Type II diabetes.…”
Section: Commercial Products For Chronic Wounds Treatmentmentioning
confidence: 99%
“…[ 88 ] Another unique feature of Matrion is that during rehydration it doesn't get folded or rolled up, thus having fewer chances of migration away from the injury site. [ 89 ] A current trial is underway to examine the safety and efficacy of Matrion in managing diabetic foot ulcers and lower extremity wounds. The trial involves 120 participants aged 21–80 years who have full‐thickness wounds due to Type I or Type II diabetes.…”
Section: Commercial Products For Chronic Wounds Treatmentmentioning
confidence: 99%
“…Similarly, a randomised controlled clinical trial investigating UC-MSCs reported improved survival rate, reduced length of stay and ventilator use as well as a decrease in IL-6 in patients who received UC-MSCs in COVID-19 ARDS (NCT04457609) [ 36 ]. Moreover, Mesoblast have reported positive initial findings from their phase 3 randomised, double-blind, placebo-controlled trial investigating Remestemcel-L in COVID-19 ARDS at international conferences (NCT04371393) [ 37 ]. Importantly, the work from Calfee and colleagues and others supports the idea of identifying phenotypes of ARDS [ 38 , 39 ] or treatable traits [ 40 ] and using that information to facilitate a personalised medicine approach.…”
Section: The Progress In the Clinical Translation Of Mscs For Inflammatory Lung Diseasementioning
confidence: 99%